Statistics and Society: Features of Interaction and Problems of Mutual Understanding - М. V. Karmanov (Статистика и экономика)
The interaction of statistics and society has always had its own historical features, and brought to life specific problems of mutual understanding, which were predetermined by many factors related to the conditions, level and quality of life of the population. In this aspect, a critical analysis of the place and role of the institution of statistics in society is of current importance, especially from the standpoint of claims made by citizens to officially published statistical information.